Discovery and Optimization of NAD+-Dependent DNA Ligase Inhibitors as Novel Antibacterial Compounds - Bi, Fangchao; Ma, Ruixin; Ma, Shutao (Current Pharmaceutical Design, 2017)
With the serious problem of multiple drug resistance to antibiotics among pathogenic bacteria spreading across the world over the past 30 years, it is crucial to search for novel inhibitors with distinct modes of action from diverse chemical classes. NAD+-dependent DNA ligases (LigAs) are essential enzymes in bacteria, vital for DNA replication and repair. Additionally, LigAs exclusively exist in eubacteria and some viruses and are not found in humans. Those enzymes have therefore been identified as attractive antibacterial drug targets. In this review we explore the discovered inhibitors of LigA through high-throughput screening or virtual screening respectively and their further structure optimization.
Keywords: antibacterial